Beyond Symptom Management: Patience and Social Support as Modifiable Buffers Against Adolescent Depressive Tendencies - Ardian, Shina Putri; Uyun, Quratul (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Abstract: Adolescent depressive tendencies often persist as sub-clinical shadows, yet they represent a critical window for preventative action. While depression is a complex, multifactorial disorder, identifying accessible protective levers is essential for public health. This study evaluates the predictive power of patience (an internal regulator) and social support (an external resource) in mitigating depressive tendencies among 259 Indonesian adolescents (ages 15–18). Utilizing multiple linear regression, our findings demonstrate that both patience (β = -0.150, p = 0.021) and social support (β = -0.163, p = 0.012) are significant negative predictors of depressive symptoms. Notably, while these variables account for a modest portion of total variance, they represent vital entry points for non-clinical interventions. The data suggests that the synergy between internal cognitive endurance and external social scaffolding creates a robust "protective buffer" against mental health decline. This research advocates for a shift toward "resilience-first" mental health policies, recommending the integration of character-based emotional regulation and peer-support networks within educational frameworks to intercept the progression toward clinical depression Keywords: adolescent depression, patience, social support